(untitled) (European Journal of Marketing and Economics, 2022)
With the economic globalization, the relationship among all countries has become more and more closed (this phenomenon is often called “global village”). The wealth also flows more freely than that of before in the world. Due to this, there is a better improvement in our everyday life. But it also raises many livelihood issues such as the wealth gap. At present, the wealth gap problem has become one of the biggest serious problems in each country, especially, in the developing countries. Because of this, quantities of scholars and economists spare no effects to explore the dynamic relationship between wealth gap and economic growth. In this, this paper sets China who is the biggest developing country in the world with bigger wealth gap as an example. The annual time series data from 1980 to 2016 is applied to analyze the dynamic operating mechanism between wealth gap and economic growth in China. All datum are sourced from the National Bureau of Statistics of the People’s Republic of China. Using the vector error correction model to conduct an empirical analysis, the dynamic operating mechanism between them will be fully understood. Then, the results of this empirical study will provide some ideas as reference for China’s government to settle the wealth gap.